Phase formation, microstructure and electrical properties of BNT-SBT ceramics prepared via the solid-state combustion technique. Issue 1 (10th December 2022) - Sinkruason, Thanapon; Junngern, Jeeranan; Sumang, Rattiphorn; Charoenthai, Nipaphat; Bongkarn, Theerachai
Abstract: Lead-free ceramics of 0.6Bi0.5 Na0.5 TiO3 -0.4Sr0.7 Bi0.2 TiO3 (BNT-SBT) were prepared by the solid-state combustion technique using glycine as fuel. The samples were calcined and sintered from 700 to 900 °C for 2 h and from 1100 to 1175 °C for 2 h, respectively. Their phase structure, microstructure and electrical properties were investigated. The XRD and Rietveld refinement results of the ceramic samples showed coexisting rhombohedral and tetragonal phases, with a ratio of 56:44 at a sintering temperature of 1150 °C. The average grain size and the measured density increased with increased sintering temperatures. The highest dielectric, ferroelectric and energy storage properties ( ε max =3142 and tan δ max =0.041, P max =27.09 μC/cm 2, W total =1.099 J/cm 3, η = 81.3% and P es =1.16%) were obtained from the sample sintered at 1150 °C.